Bulk crystal growth of hybrid perovskite material CH3NH3PbI3. Issue 3 (26th November 2014) - Dang, Yangyang; Liu, Yang; Sun, Youxuan; Yuan, Dongsheng; Liu, Xiaolong; Lu, Weiqun; Liu, Guangfeng; Xia, Haibing; Tao, Xutang
Abstract : Bulk crystal of tetragonal CH3 NH3 PbI3 with dimensions of centimeters grown by a temperature-lowering method in HI solution is reported for the first time. Abstract : Organic–inorganic hybrid perovskite materials have been receiving considerable attention due to their promising applications in many optoelectronic fields. However, some of the fundamental properties of perovskite materials are still disputed, because most of them are derived from a thin-film state. To comprehend the intrinsic characteristics in a single crystal, herein we report, for the first time, the bulk crystal growth of CH3 NH3 PbI3 . Single crystals of tetragonal CH3 NH3 PbI3 with dimensions of 10 mm × 10 mm × 8 mm were grown by a temperature-lowering method in HI solution. Studies in to the refinement and orientations of the CH3 NH3 PbI3 single crystal structure were conducted based on a high quality crystal. The absorption edge of a CH3 NH3 PbI3 single crystal was located at about 836 nm, indicating that the band gap of CH3 NH3 PbI3 is approximately 1.48 eV, which is close to the theoretical results and smaller than those derived from polycrystalline and thin-films. CH3 NH3 PbI3 crystal exhibits a relatively wide absorption (from 250 nm to 800 nm) and a relatively good thermal stability.